Desentralisasi Fiskal di Sumatera Barat: Analisis Permasalahan dan Solusi Pengelolaan Keuangan Nagari - Vanny, Dasti; Frinaldi, Aldri; Magriasti, Lince; Naldi, Hendra (PUBLICNESS: Journal of Public Administration Studies, 2025)
Fiscal decentralization is one of the key policies in the regional autonomy system implemented in Indonesia, aimed at improving efficiency and equitable development at the regional level. One of the regions implementing fiscal decentralization is West Sumatra, known for its Nagari system as a village-level government unit that plays a strategic role in the management of local financial resources. However, despite the goal of fiscal decentralization in West Sumatra to enhance regional financial independence, several issues arise concerning the management and distribution of Nagari finances. The primary challenges faced include uneven allocation of funds from the central government, limited financial management capacity at the Nagari level, and poor quality of financial reporting and accountability, which impact the transparency and accountability of fund management. This article aims to analyze these issues and propose solutions related to financial management in Nagari as an effort to improve the effectiveness of fiscal decentralization in West Sumatra. Using a qualitative approach, this study identifies factors influencing the financial performance of Nagari, including fiscal policies, human resources, and existing institutional structures. Furthermore, this article also provides recommendations for strengthening the capacity of Nagari apparatus, improving financial information systems based on technology, and enhancing coordination between local and central governments to ensure a more equitable and fair distribution of budgets.